1998
DOI: 10.1093/humupd/4.5.480
|View full text |Cite
|
Sign up to set email alerts
|

Human uterine lymphocytes

Abstract: During the luteal phase and the early months of pregnancy, there is a dense mucosal infiltration of CD56+ natural killer (NK) cells. These uterine NK cells have a phenotype (CD56bright, CD16-, mCD3-) which distinguishes them from peripheral blood NK cells (CD56dim, CD16bright, mCD3-). The uterine NK cells are in close association with extravillous trophoblast (EVT) cells which infiltrate into the decidua and maternal spiral arteries. This subpopulation of trophoblast expresses two human leukocyte antigen (HLA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
87
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(96 citation statements)
references
References 43 publications
4
87
0
5
Order By: Relevance
“…Although hematopoeitic stem cells occur in human uteri (25), in vitro assays show that human CD56 bright blood NK cells, the minor blood NK cell type, gain in functional interactions with endothelium of the decidua basalis at the preovulatory menstrual cycle surge in luteinizing hormone. This gain in potential for NK cell egress into decidua predicts uterine receptivity for transferred embryos (26) and is consistent with the dominance of CD56 bright NK cell subset in decidua (27).…”
supporting
confidence: 72%
“…Although hematopoeitic stem cells occur in human uteri (25), in vitro assays show that human CD56 bright blood NK cells, the minor blood NK cell type, gain in functional interactions with endothelium of the decidua basalis at the preovulatory menstrual cycle surge in luteinizing hormone. This gain in potential for NK cell egress into decidua predicts uterine receptivity for transferred embryos (26) and is consistent with the dominance of CD56 bright NK cell subset in decidua (27).…”
supporting
confidence: 72%
“…HLA-G is expressed primarily on trophoblast cells of the fetus that invade maternal decidua during early pregnancy. Signaling through KIR2DL4 might be of particular relevance in that context because NK cells represent Ͼ80% of decidual lymphocytes and contact invading fetal trophoblast cells during pregnancy (32,33). Ponte et al (17) have reported expression of KIR2DL4 (also called p49) on NK cells present at the maternal-fetal interface, but not on peripheral NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since the HLA-E/G nonamer complex can evoke an inhibitory or stimulatory response from NK cells (14) and since relative surface levels are likely to directly influence the efficiency of either inhibition or stimulation via CD94-NKG2, it is plausible that there is significant room for modulation of function in the arena of the maternal-placental immune interaction. Indeed, a unique NK response is associated with pregnancy (48), and rather than acting to inhibit NK activity in the maternal decidua, HLA-E may indeed act to stimulate NK to secrete cytokines appropriate for a stable immunological environment. The proper balance of inhibition and stimulation to yield a stable pregnancy may require higher or lower levels of HLA-E, depending upon other immunological and genetic factors present, thus conceivably providing strong selection on a newly introduced HLA-E allele.…”
Section: Discussionmentioning
confidence: 99%